The use of e-learning with "PAKSOBRI" to improve of students learning outcomes on Linear Algebra at Wisnuwardhana University - Octavianti, Cynthia Tri; Wulandari, Yunita Oktavia; Khasanah, Fitria (International Journal for Educational and Vocational Studies, 2022)
This study aims to determine the improvement of elementary linear algebra learning outcomes by applying Elearning with PAKSOBRI. The subjects of this study were 11 students of mathematics education class 2019/2020. The data was collected using the PAKSOBRI method (Graduated Question Package) with three questions in the form of multiple-choice, short answer, and essay questions with easy, medium and complex levels of difficulty. This type of research is CAR with data analyzed using quantitative descriptive statistics, namely by looking for the mean, median, mode, absorption and learning completeness. The indicators of the success of this research include individual mastery reaching 70, absorption reaching 70% and learning completeness 80%. Outcome student learning cycle I average 73.54, and learning completeness was 36.26%  in the deficient category. Outcome student learning cycle II average 74, and learning completeness was 72.73%  in the high category. Outcome student learning cycle III average 85.91, and learning completeness was 81.82%  in the high category. The conclusion shows an increase in elementary linear algebra learning outcomes for students of mathematics education, class 2019/2020 through E-learning application with PAKSOBRI.